EXPLORING THE LINK BETWEEN SERVICE QUALITY AND CONSUMER BEHAVIOR IN WHITE PETROLEUM OUTLETS IN DELTA STATE - Okonkwo , Chinedu Emmanuel; Efeoghene, Grace Oghenekaro (International Research Journal of Arts and Communication, 2025)
The study focused on the influence of service quality on customer patronage of white petroleum products service stations in Delta State, Nigeria. The business of petroleum products retailing has become highly competitive and following the removal of fuel subsidies which drastically increased the pump prices of petroleum products, there is more consideration and demand for better service delivery from petroleum products retailers. Petroleum products service stations tend to differ from the usual filling stations that retail petroleum products by their capacity (numbers of dispensing pumps) and services they offer to customers such as lube services, vulcanizing services, minimarket, convenience services, customer care services, minor repairs, etc, these services are meant to compliment the sales of petroleum products. Thus, this study examined the impact of service quality on customer patronage of petroleum products service stations in Delta State, Nigeria. The servqual model dimension of service was adopted for this study as (service responsiveness, service assurance, service reliability, service tangibility, and service empathy) as the independent variables against customer patronage as the dependent variable. Petroleum products service stations were selected from Asaba, Ughelli, Sapele, and Warri areas of the State. Questionnaire were administered on customers of the selected service stations using a sample size of 400. Data gathered were analyzed using regression analysis (SPSS version 25). The result of the study showed that there is significant positive relationship between service quality and customer patronage of petroleum products service stations in the areas under review. It was concluded that service responsiveness, service assurance, service reliability, and service tangibility influence customer patronage of petroleum products service stations in Delta State, Nigeria. Based on the findings, we recommended that existing and potential petroleum products service stations to continually train their sale and service people to improve and enhance consistency in their service quality which has been identified as useful in attracting and retaining customers which is in line with the objective function of the firms. This study investigates Sales promotion techniques and brand recognition of electronic stores in Rivers State.